1997
DOI: 10.1523/jneurosci.17-12-04785.1997
|View full text |Cite
|
Sign up to set email alerts
|

GABA Activity Mediating Cytosolic Ca2+Rises in Developing Neurons Is Modulated by cAMP-Dependent Signal Transduction

Abstract: In the majority of developing neurons, GABA can exert depolarizing actions, thereby raising neuronal Ca 2ϩ . Ca 2ϩ elevations can have broad consequences during development, inducing gene expression, altering neurite outgrowth and growth cone turning, activating enzyme pathways, and influencing neuronal survival. We used fura-2 and fluo-3 Ca 2ϩ digital imaging to assess the effects of inhibiting or activating the cAMP signal transduction pathway on GABA activity mediating Ca 2ϩ rises during the early stages of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
1

Year Published

1999
1999
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(30 citation statements)
references
References 69 publications
2
27
1
Order By: Relevance
“…In support of our hypothesis, studies have shown that GABA activity mediating cytosolic Ca 2ϩ increases in developing neurons is triggered by changes (activation or inhibition) in cAMP-dependent signal transduction. 49 The de novo acquisition of proliferative and secretory phenotypes of large cholangiocytes by small cholangiocytes is likely attributable to the IP 3 /Ca 2ϩ -dependent activation of AC8, a Ca 2ϩ -dependent AC isoform that plays a key role in the proliferative and secretory functions of large bile ducts. 17 Nine AC isoforms exist in mammalian cells.…”
Section: Discussionmentioning
confidence: 99%
“…In support of our hypothesis, studies have shown that GABA activity mediating cytosolic Ca 2ϩ increases in developing neurons is triggered by changes (activation or inhibition) in cAMP-dependent signal transduction. 49 The de novo acquisition of proliferative and secretory phenotypes of large cholangiocytes by small cholangiocytes is likely attributable to the IP 3 /Ca 2ϩ -dependent activation of AC8, a Ca 2ϩ -dependent AC isoform that plays a key role in the proliferative and secretory functions of large bile ducts. 17 Nine AC isoforms exist in mammalian cells.…”
Section: Discussionmentioning
confidence: 99%
“…In the present experiments, however, forskolin alone was able to mimic the effects of BDNF, and STD-LTP was prevented when the postsynaptic cell was loaded with the membrane impermeable PKA inhibitor PKI 6 -22. This suggests that cAMPdependent PKA may regulate intracellular calcium rise (Obrietan and van den Pol, 1997;Dunn et al, 2006), which in turn would affect BDNF release from the postsynaptic cell. The precise molecular mechanisms regulating this cascade remain to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore we found that AEA stimulated GABA release in our experimental conditions. Obrietan and van den Pol (29) suggested that cAMP, the second messenger linked to cannabinoid receptors, could inhibit GABA release. The inhibition of LHRH release by AEA and EtOH from the hypothalamus is mediated in part by CB1-r inhibiting AC.…”
Section: Discussionmentioning
confidence: 99%